Enhancing Students’ Listening Skill Through Podcasts - Indriana, Pathul; Saori, Sopian (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study investigates the effectiveness of podcasts in improving the listening skills of English as a Foreign Language (EFL) learners. The research was conducted at Yusuf Abdussatar Islamic Vocational School in Kediri West Lombok Indonesia Indonesia (n=35, Grade 11), the research employed an experimental design with interviews and questionnaires. The findings reveal that majority of students (55%) perceived podcasts as facilitating easier learning, further integration strategies could be explored for optimal benefit. Although 75% found podcasts somewhat effective and enjoyable, further research could identify aspects to maximize their impact. Encouragingly, all students agreed that podcasts could improve listening skills. Additionally, 90% of participants reported increased motivation to learn further after using podcasts. The study also revealed positive perceptions regarding podcasts' contribution to keeping up with educational media trends (16.7% strongly agreed) and fostering independent learning (83.3% agreed or strongly agreed). These findings suggest that podcasts can be a valuable tool for EFL classrooms. Conclusion: Incorporating podcasts into EFL classrooms appears to be a promising method for improving listening skills and fostering a positive learning environment.